Development of a new intermediate‐scale box test on sandwich panel products compared with ISO 13784‐1 room test and EN 13501‐1 classification system. (18th May 2021) - Yoshioka, Hideki; Noguchi, Takafumi; Kobayashi, Kyoichi; Kanematsu, Manabu; Ando, Tatsuo; Pareek, Sanjay; Hayakawa, Tetsuya
Summary: With respect to the reaction to fire performance of sandwich panel products, in ISO/TC92/SC1/WG7 "Large and intermediate scale fire test methods, " ISO 13784‐1 "Reaction to fire test for sandwich panel building systems—Part 1: Small room test" is specified as a method of test for determining the reaction to fire behavior of sandwich panel building systems. On the other hand, according to EN 13501‐1 "Fire classification of construction products and building elements, " EN 13823 (SBI test) and EN ISO 11925‐2 (ignitability test) are used especially for evaluating the classes B, C, and D in the Euroclass system. The authors have developed a new intermediate‐scale box test for sandwich panel products, pertaining to the correlation with ISO 13784‐1 especially on the flashover occurrence, which was locally standardized as JIS A 1320:2017, and is now internationally being discussed as ISO/WD TS 23657 at ISO/TC92/SC1/WG7. In this paper, regarding five sandwich panel specimens, various fire tests were conducted according to ISO 13784‐1, EN 13501‐1, and ISO/WD TS 23657, and those results were compared with each other, indicating that ISO/WD TS 23657 has a good correlation with ISO 13784‐1 in terms of flashover, and that evaluation results based on ISO/WD TS 23657 could be similar to those based on EN 13501‐1. Furthermore, a new tentative classification system was proposed based on those limited experimental results conducted in this research.